Prácticas de conservación ambiental en la comunidad de Santa Ana I zona, del Río Tahuayo, Loreto, 2024 - Fasanando Perez, Evelyn Margoth (2025)
This study examines environmental conservation practices in the Santa Ana I Zone community, in the Tahuayo River Basin, Loreto, Peru, through a cross-sectional and non-experimental quantitative research. The results reveal that, despite facing high levels of poverty and dependence on craftsmanship, the community shows strong awareness of environmental issues such as deforestation and water pollution. However, active participation in conservation initiatives is limited due to a lack of resources and education. Notable conservation practices include the planting of fruit and timber trees, as well as the use and transmission of knowledge about medicinal plants, which contribute to both ecological regeneration and economic sustainability. This study highlights the importance of educational and empowerment programs to integrate environmental conservation with local economic development, contributing to the design of public policies for rural Amazonian communities.